Intra-arterial or intravenous thrombolysis for acute ischemic stroke? The SYNTHESIS pilot trial. (30th October 2009) - Ciccone, A; Valvassori, L; Ponzio, M; Ballabio, E; Gasparotti, R; Sessa, M; Scomazzoni, F; Tiraboschi, P; Sterzi, R; ,
Abstract : Objective: To assess the feasibility, safety and preliminary efficacy of intra-arterial thrombolysis (IAT) compared with standard intravenous thrombolysis (IVT) for acute ischemic stroke. Methods: Eligible patients with ischemic stroke, who were devoid of contraindications, started IVT within 3 h or IAT as soon as possible within 6 h. Patients were randomized within 3 h of onset to receive either intravenous alteplase, in accordance with the current European labeling, or up to 0.9 mg/kg intra-arterial alteplase (maximum 90 mg), over 60 min into the thrombus, if necessary with mechanical clot disruption and/or retrieval. The purpose of the study was to determine the proportion of favorable outcome at 90 days. Safety endpoints included symptomatic intracranial hemorrhage (SICH), death and other serious adverse events. Results: 54 patients (25 IAT) were enrolled. Median time from stroke onset to start to treatment was 3 h 15 min for IAT and 2 h 35 min for IVT (p<0.001). Almost twice as many patients on IAT as those on IVT survived without residual disability (12/25 vs 8/29; OR 3.2; 95% CI 0.9 to 11.4; p=0.067). SICH occurred in 2/25 patients on IAT and in 4/29 on IVT (OR 0.5; CI 0.1 to 3.3; p=0.675). Mortality at day 7 was 5/25 (IAT) compared with 4/29 (IVT) (OR 1.6; CI 0.4 to 6.7; p=0.718). There was no significant difference in the rate of other serious adverse events. Conclusions: Rapid initiation of IAT is a safe and feasible alternative to IVT in acute ischemic stroke. Trial registration number NCT00540527.